Spatial and temporal variability of soil loss in gully erosion in Upper Blue Nile Basin, Ethiopia - Bogale, A.; Aynalem, D.; Adem, Anwar A.; Mekuria, Wolde; Tilahun, S. (Springer, 2020)
Gully erosion has many negative impacts on both cultivated and grazing lands in Ethiopian highlands. The present study was conducted in Chentale watershed, Ethiopia, to quantify the contribution of gully erosion, and to assess its temporal changes. Within the Chentale watershed, we selected a sub-watershed (104.6 ha) and nested gully catchment, and gauged for stream flow and sediment concentration data in 2015 and 2016. We measured gully dimensions before and after the onset of the rainy season in 2016 to determine soil loss due to gully erosion. The temporal changes of gully expansion were determined by digitizing gully plain area from Google earth images taken in 2005 and 2013. The results support that gullies were expanding at higher rate in recent years. Area covered by gullies in the watershed increased from 1.84 to 3.43 ha between 2005 and 2013, indicating that the proportion of the watershed covered by gullies was nearly doubled in the investigated period. The estimated soil loss from the main watershed and gullies catchment was 6 and 2 t ha-1 year-1 in 2015, and was 7 and 9 t ha-1 year-1 in 2016, respectively. The results support that gullies were the main contributors of soil erosion in the watershed, and that integrated soil and water conservation measures are required to reduce soil erosion.